Wage Cyclicality and Labor Market Sorting: Comment - Jonathan S. Hartley; Matthew A. Olson (Institute for Replication (I4R), 2023)
Figueiredo (2022) examines wage cyclicality across the skill mismatch distribution finding large differences. Some key results include finding that wages are acyclical in good labor market matches but procyclical in poor matches. Using the public replication material provided by the authors, we were able to exactly duplicate the results of the study. Further, using several further robustness checks, such as subtracting (potentially correlated) covariates in the regressions, using different standard errors (rather than clustered ones), or different time periods of the data left the key results largely unchanged with some minor caveats.
Keywords: 330